3x + y = 0
3x - y = 0
- - - - - - -
6x = 0
6x/6 = 0 / 6
x = 0
The answer is x = 0
Insert the x value into equation 1
- - - - - - - - - - - - - -- - - - - - - -
3x + y = 0
3(0) + y = 0
0 + y = 0
y = 0
The answer is y = 0
Insert the y value into equation 1
- - - - - - - - - - - - - - - - - - - - -
Check for equation 1
3x + y = 0
3(0) + 0 = 0
0 + 0 = 0
0 = 0
- - - - - - - - - - -
Check for equation 2
3x - y = 0
3(0) - 0 = 0
0 - 0 = 0
0 = 0
- - - - - - - - - - - - -
The solution set is { 0, 0 }
- - - - - - - - - -s-
2007-01-20 06:47:23
·
answer #1
·
answered by SAMUEL D 7
·
1⤊
0⤋
If you read this earlier, I was wrong! So here is the revision. If 3x + y = 0 and 3x-y = 0 then
3x + y must equal 3x -y
3x + y = 3x -y
Subtract 3x from both sides.
Now y = -y
Now add y to each side.
2y = 0
Divide both sides by 2.
y = 0/2 which is 0. So y = 0.
Now plug 0 in for y in the original equation.
3x + 0 = 0 So 3x = 0
Divide each side by 3.
x = 0/3
so x = 0.
There is one answer. (0,0)
2007-01-20 04:58:35
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
In fact x and y =0 are the solutions for your sets of equation - one solution only
2007-01-20 04:57:42
·
answer #3
·
answered by sm bn 6
·
1⤊
0⤋
we add the two equations and get
6x=0 so x=0
0+y=0
0-y=0
y=0
A)one solution x=y=0
2007-01-20 04:54:32
·
answer #4
·
answered by Monica 1
·
1⤊
0⤋
It has one: 0,0.
To see this, add the 2 equations to get 6x=0,
x = 0. Plug this back into either equation to get y=0.
2007-01-20 05:04:18
·
answer #5
·
answered by steiner1745 7
·
0⤊
0⤋
A, one solution
since for infinite or none, the slope need to be equal
2007-01-20 04:54:59
·
answer #6
·
answered by Taras 2
·
1⤊
0⤋
zero is the answer right? so One solution
2007-01-20 05:11:42
·
answer #7
·
answered by Cardinals fan 2
·
0⤊
1⤋
A
0,0
2007-01-20 05:05:50
·
answer #8
·
answered by ag_iitkgp 7
·
0⤊
1⤋